ESTUDIO DE FACTIBILIDAD PARA LA CREACION DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE GALLETAS DE AMARANTO EN LA CIUDAD DE LOJA - Sinche Aguirre, Katty Lorena (2015)
By developing a new investment project in the city of Loja wealth is generated and new sources of employment and the most important thing is to accommodate adequately to consumers, thus improves the quality of life of the inhabitants are set City creating jobs, plus it encourages micro enterprise development and thus reduce migration in the city of Loja. This investment project addresses environmental problems in order to contribute to sustainable development of the city of Loja, interacting with the community, in order to generate alternative solutions to problems that impede social development, it is intended to carry out a project contributing to generate value in organizations, to the diversification and revitalization of the economy that generates social welfare. Considering the "FEASIBILITY STUDY FOR CREATING A producer and marketer AMARANTH COOKIES IN THE CITY OF LOJA" It is important to consider the economic contribution to this investment project will take place at the forefront suppliers of raw material for the production of "cookies Amaranto" since the current economy of families will be improved. As it seeks to develop a product that is accessible to consumers of the city of Loja. The creation of new production units related product with the consumer profile by offering products with features that adequately meet consumer needs, at affordable prices without generating major impact on its economy. It should be noted that the biscuits are based Amaranth own proteins and minerals of raw materials such as: Amaranth, which contribute to development. The main objective was to determine the feasibility of creating a producer and marketer of biscuits amaranth company in the city of Loja well as the specific objectives, including left, perform a market study which determined that 97% of respondents agree the implementation of the producer and marketer of biscuits Amaranto company that the existing companies do not provide or offer this product, running the technical study where an installed capacity to produce 4.380.000 million cookies to be determined, while capacity utilization of first year of life is considered to begin at 40% and will increase annually by 5%, it 5 stressed that the company will be located in the city of Loja and Esmeraldas specifically in Marcabeli streets. In addition an administrative law firm where the highlights is the legal constitution of the company with which it is stated that the company name with which it will be recorded will be "WEALTH OF AMARANTO CIA.LTDA", which is recorded as designed a small business that will have six employees, a financial study in which different budgets with actual values of the local market developed, determining a total investment of $ 50.975,75 US dollars, comprising an equity capital by 71% was performed and the rest with a loan from the Development Bank at an interest rate of 11.83. According to financial indicators, it was determined that the NPV will be $ 54.883,04 while the IRR of 75,13% will be demonstrating that the project is feasible and beneficial to any investor who wants to carry it out, noting that the investment will be recovered in estimated period of 3 years, 8 months and 12 days, while below five years of life posed. As the final part of this thesis has been plated respective conclusions and recommendations that have been achieved during its development, thus providing the necessary sequence to the project and above all showing the benefits they provide to society it is to meet your needs fully.